Natural Resources and Economic Growth: The Role of Investment. - Thorvaldur Gylfason; Gylfi Zoega (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
Empirical evidence seems to indicate that economic growth since 1965 has varied inversely with natural resource abundance across countries. This paper proposes a linkage between abundant natural resources and economic growth, through saving and investment. When the share of output that accrues to the owners of natural resources rises, the demand for capital falls leading to lower real interest rates and less rapid growth. However, institutional reforms paving the way to a more efficient allocation of capital may enhance the quantity as well as the quality of new investment and sustain growth. Empirical evidence from 85 countries from 1965 to 1998 suggests that abundant natural capital may on average crowd out physical capital thereby inhibiting economic growth. The results also suggest that abundant natural resources may hurt saving and investment indirectly by slowing down the development of the financial system. However, high growth rates in a handful of formerly resource-dependent economies seem to indicate that economic and structural reforms can overcome any adverse effect of natural resources on economic growth.
Keywords: 330